A conserved island of BAG6/Scythe is related to ubiquitin domains and participates in short hydrophobicity recognition. (31st December 2015) - Tanaka, Hirofumi; Takahashi, Toshiki; Xie, Yiming; Minami, Ryosuke; Yanagi, Yuko; Hayashishita, Mizuki; Suzuki, Rigel; Yokota, Naoto; Shimada, Masumi; Mizushima, Tsunehiro; Kuwabara, Naoyuki; Kato, Ryuichi; et al.
Abstract : BAG6 (also called Scythe) interacts with the exposed hydrophobic regions of newly synthesized proteins and escorts them to the degradation machinery through mechanisms that remain to be elucidated. In this study, we provide evidence that BAG6 physically interacts with the model defective protein substrate CL1 in a manner that depends directly on its short hydrophobicity. We found that the N terminus of BAG6 contains an evolutionarily conserved island tentatively designated the BAG6 ubiquitin‐linked domain. Partial deletion of this domain in the BAG6 N‐terminal fragment abolished in cell recognition of polyubiquitinated polypeptides as well as the hydrophobicity‐mediated recognition of the CL1 degron in cell and in vitro . These observations suggest a mechanism whereby the BAG6 ubiquitin‐linked domain provides a platform for discriminating substrates with shorter hydrophobicity stretches as a signal for defective proteins. Abstract : The C‐terminus of BAG6 has been shown to be involved in TA transmembrane domain (TMD) protein biogenesis. Here, we show that newly identified ubiquitin‐related domains in the N‐terminus of BAG6/Scythe contributes short hydrophobicity recognition of defective proteins.